Microwave-assisted synthesis and anti-inflammatory activity evaluation of some novel α-aminophosphonates. (3rd October 2017) - Sujatha, B.; Mohan, S.; Subramanyam, Ch.; Rao, K. Prasada
GRAPHICAL ABSTRACT: ABSTRACT: An expeditious green synthetic approach was developed for the synthesis of α-aminophosphonates in good yields through one-pot three component reaction (Kabachnik-Fields reaction) of equimolar quantities of N -(4-amino-2-phenoxy phenyl)methanesulfonamide, diethylphosphite and various aldehydes under conventional as well as microwave irradiation methods. The newly synthesized compounds were characterized by NMR ( 31 P, 1 H, and 13 C), Mass, IR and C, H, N analyses. The synthesized compounds were screened for their anti-inflammatory activity using rat paw edema method. Most of the compounds from the series showed good anti-inflammatory activity when compared with standard drug. Especially the compounds5d bearing 4-hydroxy-3-nitrophenyl moiety, 5e bearing 3-bromo-4-fluorophenyl moiety, 5g incorporated with 2, 4-dichlorophenyl moiety and5f containing 4-chlorophenyl moiety exhibiting edema inhibition of 91.01% to 85.39% after 4 h of carrageenan injection while the other compounds displayed inhibition ≥75%.